(untitled) (Revista Sistemas de Producción Agroecológicos, 2020)
Dual-purpose livestock in Colombia is located in regions of the low tropics, such as in the valleys of the Magdalena and Cauca rivers, the Atlantic Coast and the plains, where the zone of foot of the plain in the department of Meta is located, which is characterized by the fact that milk production is It is mainly made with dual purpose cattle which are crosses of Bos Taurus with Bos indicus, where the cows are hand-milked once a day and the calves remain with their mothers for around 9 months of age. Although the nutritional qualities of milk and its derivatives are of excellent nutritional quality, there are risks for a safe production, mainly in these tropical zones where cattle ranching is done extensively and milk management cannot be the best due to the Lack of infrastructure for the conservation of this product, therefore the risk of contamination and multiplication of microorganisms can be increased, which are detected in the laboratory by counting colony forming units (CFU), the presence of total coliforms and fecal, microorganisms that can alter the physical-chemical quality of its components: density, fat and non-fat solids, this article aims to explain in a didactic way how some nutritional and microbiological analyzes are carried out to determine the quality of milk in the Laboratory and its importance for a production innocuous, and that are in the field of concern of Animal Production and Veterinary Sciences, since there are clearly demands from the social and productive systems to which these professionals must be attentive, since the concepts of quality and health are linked in all the milk production chain.